COOKIES SUMBER KALIUMBERBASIS TEPUNG PISANG (Musa paradisiaca), TEPUNG MAIZENA (Zea mays), DAN KACANG HIJAU (Phaseolus radiatus L.) - Vitria Melani; Intan Ali Ramadhiany; Erry Yudhya Mulyani; Putri Ronitawati (Jurnal Gizi dan Pangan Soedirman, 2022)
Hypertension is a condition where systolic blood pressure greater than 140 mmHg and diastolic blood pressure greater than 90 mmHg. One of the factors that can prevent hypertension is potassium deficiency. Foods that contain high potassium are bananas and mung beans. These foods can be developed as raw ingredients for making cookies for people with hypertension. In addition, cornstarch is used as a carbohydrate source which is commonly used in the making of snacks. The objective of this study is to determine the effect of adding banana flour and cornstarch to cookie’s nutritional and organoleptic content. The addition of mung beans is the same for all formulations. An experimental study with four formulations which are F0, F1, F2 and F3. This study involved 25 semi-trained panelists and 30 consumer panelists for organoleptic testing. Data analysis using ANOVA and Duncan test. Based on the ANOVA test results, there were significant differences in preference, quality and nutritional value between the four formulations. The selected cookie formulation is F2 with a ratio of 80% banana flour and 20% cornstarch which contains 442 kcal, protein 4.28 g, fat 16.82 g. 68.5 g carbohydrates, 0.25 g fiber and 4016 mg potassium per 100 g cookies.